2006
DOI: 10.1097/01.mej.0000192049.04729.0c
|View full text |Cite
|
Sign up to set email alerts
|

Personal digital assistants change management more often than paper texts and foster patient confidence

Abstract: Personal digital assistants are feasible in an academic emergency department and change management more often than texts. EMRs accessed personal digital assistants more often than paper texts. Patient perceptions of physicians who use personal digital assistants are neutral or favorable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 10 publications
2
23
0
1
Order By: Relevance
“…For example, a MEDLINE search combining ''attitude to computers'' and ''emergency medicine'' identified only two articles: one comparing personal digital assistants with paper texts and a second assessing a computer-aided instructional program for the pediatric ED. 6,7 Similarly, a second search combining ''computer literacy'' and ''emergency medicine'' also brought up two articles. A 1993 survey reported that medical school computer training was variable and recommended implementing a residency-based computer curriculum.…”
Section: Recommendationmentioning
confidence: 99%
“…For example, a MEDLINE search combining ''attitude to computers'' and ''emergency medicine'' identified only two articles: one comparing personal digital assistants with paper texts and a second assessing a computer-aided instructional program for the pediatric ED. 6,7 Similarly, a second search combining ''computer literacy'' and ''emergency medicine'' also brought up two articles. A 1993 survey reported that medical school computer training was variable and recommended implementing a residency-based computer curriculum.…”
Section: Recommendationmentioning
confidence: 99%
“…PDAs decrease medication errors, 3 allow faster access to medical reference material, and augment patient confidence. 4 Medical students feel that PDA use enhances their clinical clerkship experiences. 5 Approximately 60-70% of medical students and residents utilize PDAs in support of undergraduate or graduate medical education in both the preclinical and clinical environments.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, one [41] compared daily and weekly registrations of self-reported health status measures between PDA and paper-pencil (PP) format regarding scores, variation, and feasibility; one [42] feasibility of using PDA-based system for tracking and analysis of food intake for pregnant women; one [43] compared the completeness of data collection using a paper and PDA-based system. Other studies, assessed feasibility and patient acceptance of PDAs for collection of health data [68]; one [58] evaluated the quality of data on sexual behavior data collected with PDA-based system in comparison with paper-based questionnaires; and one [61] explored the acceptability of PDA for HIV/AIDS data collection and to identified potential barriers to acceptance.…”
Section: Resultsmentioning
confidence: 99%